Level of knowledge on the role of Baitulmal Institutions among students / Wan Nor Hafifi Wan Hasan - Wan Hasan, Wan Nor Hafifi (2019)
Treasury is an important mechanism that was established officially by Caliph Saiyidina Umar Al-Khattab in order to manage the state property for economic development. However, the implementation of Baitulmal has been adapted to the requirements of the Malaysian constitution by referring to the schedule of the nine constitutions. In Malaysia, Baitulmal currently is administered by the State Islamic Religious Council. Because of that, the function and role of Baitulmal have been narrowed due to the administration of Baitulmal through the state government. Thus, this study intends to identify the level of knowledge on the Baitulmal Institutions among the community that has been specific to students. The study is being conducted in Universiti Puncak Alam, Selangor. This research is based on data obtained from a survey questionnaire that polled the public basic knowledge of Baitulmal. The data were analyzed to evaluate and determine the knowledge among the students about that Baitulmal institutions. The research suggested that the central government should play their role which is more proactive and decisive when dealing with Baitulmal affairs in Malaysia. As a result, the study found that the majority of students have a high level of knowledge about Baitulmal institutions while there is just a minority that has no idea about it.